Shaping the future: indicators of need in the third millennium. (1st September 2004) - Peet, John
In this paper, the issue of sustainability and sustainable development is addressed through the assumed goal of sustainable living. That goal implies that humanity consciously decides to adjust its collective behaviour in order to change present unsustainable practices towards those that reduce and eventually eliminate unsustainable impacts on the natural environment, while at the same time attempting to ensure that the reasonable needs of people are satisfied. In order to steer change from unsustainable to more sustainable practices, social control systems need to be in place, using key behavioural criteria to indicate the necessity (or otherwise) of fiscal, legal or other policies. Starting from an overall philosophy that acknowledges the reality of systemic complexity, this paper describes Max-Neef's taxonomy of human needs, and Bossel's more generic orientor framework for systems in general. These two, used together, enable one to evaluate the basic needs of both human, natural, economic and social systems, so that policies can be identified to address critical deficiencies.